دور الجامعة في تنمية العمل املقاوالتي لدى الطلبة دراسة حالة بجامعة عمار ثليجي - باألغواط - شرفاوي خلود; سماني فاطمة; بن لحبيب بشير (My University, 2022)
Entrepreneurship aims to acquaint students with the ways and steps of establishing small and medium enterprises, based on knowledge of the basics of entrepreneurship or entrepreneurship, its importance and characteristics, as well as terms related to entrepreneurship such as entrepreneurship spirit, entrepreneurship education and the entrepreneurial university, then introducing innovation, invention and risk-taking because entrepreneurship equals innovation plus risk. The specialized agencies in escorting students' projects (engineering, weaving...).